Production of cucumber seedlings in different substrates and tray volumes (Research, Society and Development, 2022)
Cucumber is among the vegetable species that for a long time were implanted via direct sowing and currently makes use of the production of seedlings in trays, providing better conditions for the initial development of the plant. However, due to the wide varieties of containers and substrates, doubts arise as to the best option to adopt to provide its highest performance. In view of this, the objective of this work was to evaluate the production of cucumber seedlings in different substrates and volumes of containers, aiming at production savings and final quality of the seedlings. The work was carried out in a randomized block design, with four replications, in a factorial scheme (2x4), the first factor being composed of two types of trays: 128 cells (capacity of 22.5 mL per cell) and 200 cells (capacity of 12.5mL per cell) and the second by four types of substrates (S1=poultry manure + soil (1:1); S2= ​​cattle manure + soil (1:1); S3= commercial substrate; S4= soil). The seeds used were of the emerald cucumber type caipira. The variables analyzed were number of leaves (NF), plant height (AP), root length (CR), stem diameter (DC), shoot (MFA) and root fresh mass (MFR), dry mass of shoot (MSA) and root (MSR). According to the results, it was found that the substrates and volumes of trays presented similar results, allowing the use of any of them, according to the availability of obtaining.